2012
DOI: 10.1093/carcin/bgs177
|View full text |Cite
|
Sign up to set email alerts
|

Single-CpG-resolution methylome analysis identifies clinicopathologically aggressive CpG island methylator phenotype clear cell renal cell carcinomas

Abstract: To clarify the significance of DNA methylation alterations during renal carcinogenesis, methylome analysis using single-CpG-resolution Infinium array was performed on 29 normal renal cortex tissue (C) samples, 107 non-cancerous renal cortex tissue (N) samples obtained from patients with clear cell renal cell carcinomas (RCCs) and 109 tumorous tissue (T) samples. DNA methylation levels at 4830 CpG sites were already altered in N samples compared with C samples. Unsupervised hierarchical clustering analysis base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
145
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 117 publications
(153 citation statements)
references
References 37 publications
8
145
0
Order By: Relevance
“…Specific DNA hypermethylation of CpG sites on TRH gene was only reported over last years in RCC (42), and no further clinically relevant data is available at this time.…”
Section: Thyrotropin-releasing Hormone (Prolactin-releasing Hormone-tmentioning
confidence: 98%
“…Specific DNA hypermethylation of CpG sites on TRH gene was only reported over last years in RCC (42), and no further clinically relevant data is available at this time.…”
Section: Thyrotropin-releasing Hormone (Prolactin-releasing Hormone-tmentioning
confidence: 98%
“…Whether or not aberrations of genes involved in histone modification, such as NCOA1 ,35 participate in the acquisition of epigenetic characteristics in CIMP‐positive RCCs warrants further examination. Aberrations of genes involved in cell adhesion, such as CELSR1, CELSR2 ,36 CTNND1 ,37 LAMC2 38 and TJP1 ,39 may affect the invasiveness and metastatic potential of CIMP‐positive RCCs (CIMP‐positive RCCs show invasive growth and distant metastasis more frequently than CIMP‐negative RCCs13). Moreover, genetic aberrations of microtubule‐associated proteins, such as DNAH2, DNAH5, DNAH10 ,31 RP1 32 and HAUS8 ,33, 34 may be correlated with dysregulation of the spindle checkpoint in CIMP‐positive RCCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that DNA methylation alterations play a significant role in renal carcinogenesis 9, 10. Although Morris and Maher previously reported that the relevance of the CIMP‐positive phenotype to RCCs had not yet been clearly defined,11 we first identified CIMP‐positive clear cell RCCs based on genome‐wide DNA methylation (methylome) analysis12 and showed that DNA hypermethylation of CpG islands in the FAM150A, GRM6, ZNF540, ZFP42, ZNF154, RIMS4, PCDHAC1, KHDRBS2, ASCL2, KCNQ1, PRAC, WNT3A, TRH, FAM78A, ZNF671, SLC13A5 and NKX6‐2 genes was the hallmark of CIMP in RCCs 13…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It's a transcription factor with known positive and negative regulatory activities in development and differentiation [84] and seemed to be a tumor suppressor [85] . NKX6.2 is respectively detected in a variety of different neoplasms, like brain tumor [86] , bladder cancer [87] , renal cell carcinoma [88][89] , and lung adenocarcinoma [90] . By so far, no NKX6.2 expression is reported in gastrointestinal neoplasms.…”
Section: Nkx62mentioning
confidence: 99%